High-speed rail as a solution to metropolitan passenger mobility: The case of Shenzhen-Dongguan-Huizhou metropolitan area - Lin, Xiongbin; Yang, Jiawen; MacLachlan, Ian (Journal of Transport and Land Use, 2018)
High-speed rail (HSR) has played an important role in China’s long-distance travel. However, the potential of this transport technology to meet the demand of passenger mobility at the metropolitan scale is still unclear. This research examines this potential by studying transportation investment for intercity passenger mobility in the Shenzhen-Dongguan-Huizhou Metropolitan Area, where multiple fixed guideway transit systems have been proposed and HSR service has been implemented to carry passengers between central Shenzhen and outer portions of this metropolitan region. Comparison of alternative modes explains why HSR is competitive at the metropolitan scale. Interviews with relevant stakeholders reveal the institutional conditions for utilizing the national HSR system for regional passenger mobility.